2009
DOI: 10.1039/b913305d
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected chemoselectivity in the rhodium-catalyzed transfer hydrogenation of α,β-unsaturated ketones in ionic liquids

Abstract: Chalcone and some other a,b-unsaturated ketones were subjected to transfer hydrogenation catalyzed by the dimer [Rh(cod)Cl] 2 and the Wilkinson's catalyst in imidazolium-, ammonium-and phosphonium-based ionic liquids. In certain ionic liquids, the reduction of chalcone gave 1,3diphenylpropan-1-one chemoselectively, in contrast with molecular solvents, which resulted in the formation of 1,3-diphenylpropan-1-ol. An accelerated reaction rate was observed in [emim][BuSO 4 ] and [emin][HeSO 4 ]. The observed chemos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 9 publications
0
17
1
Order By: Relevance
“…A recent example has been reported by Hermecz and co-workers. [89] A greener approach to this methodology is the combination of ionic liquids as solvents and scCO 2 for chemical separation. This ionic liquid/scCO 2 biphasic system has been applied with high success in the hydrogenation of alkenes, [90] acetophenone, [91] and asymmetric hydrogenation of tiglic acid, [92] isobutylatropic acid, [92] and N-(1-phenylethylidene)aniline (Scheme 37).…”
Section: Reductions In Ionic Liquidsmentioning
confidence: 99%
“…A recent example has been reported by Hermecz and co-workers. [89] A greener approach to this methodology is the combination of ionic liquids as solvents and scCO 2 for chemical separation. This ionic liquid/scCO 2 biphasic system has been applied with high success in the hydrogenation of alkenes, [90] acetophenone, [91] and asymmetric hydrogenation of tiglic acid, [92] isobutylatropic acid, [92] and N-(1-phenylethylidene)aniline (Scheme 37).…”
Section: Reductions In Ionic Liquidsmentioning
confidence: 99%
“…The catalytic reduction of α,β‐unsaturated ketones may proceed with the reduction of either of the carbonyl or the olefinic moiety individually or both of them together, and there exist literature precedence for all of these possibilities . For example, the pincer palladium complex of type (PCP)PdCl (PCP=1,5‐bis(diphenylmethyl)‐2,4‐dimethylbenzene) and the iridium half‐sandwich complex of the type [Cp*IrCl] 2 and an in ‐ situ generated rhodium complex of type, (NHC)Rh(PPh 3 ) 2 Cl (NHC=1‐butyl‐3‐methyl‐1H‐imidazol‐2‐ylidene) effectively reduced only the olefinic moiety of α,β‐unsaturated ketone substrate giving saturated ketones in excellent yields. Similarly, the reduction of carbonyl moiety over the olefinic bond yielded α‐hydroxy olefins in case of a ruthenium complex of the type, RuCl 2 (DPEphos) (DPEphos= bis [(2‐diphenylphosphino)phenyl] ether) and [( S , S )‐Phos‐Biox]Ru(cymene)Cl 2 ] 2 (where S , S )‐Phos‐Biox=bisphosphinobioxazoline) among many other reported examples…”
Section: Resultsmentioning
confidence: 75%
“…Furthermore, the complete reduction of the carbonyl and olefin moieties to yield the corresponding alcohol have also been reported for a handful of iridium and palladium N‐heterocyclic carbene complexes ,. The asymmetric transfer hydrogenation reduction of α,β‐unsaturated ketones to the corresponding alcohol have been reported for a handful of non‐N‐heterocyclic carbene (NHC) ligand type Ts‐DPEN (Ts‐DPEN=4‐methylphenylsulfonyl‐1,2‐diphenylethylene‐diamine) for iridium, which at 1 mol % catalyst loading at 40 °C yields fully reduced alcohol in 99% with enantioselectivites ( ee ) up to 93% .…”
Section: Resultsmentioning
confidence: 99%
“…www.intechopen.com When Hermecz et al [135] carried out hydrogenation of chalcone using Wilkinson's catalyst, they found that the reactions using only ionic liquids as solvents gave better selectivity towards 1,3-diphenylpropan-1-one than reactions performed in a mixture of molecular solvents and ionic liquids ( Figure 63). The group explained the selectivity towards 1,3-diphenylpropan-1-one, by proposing a specific interaction between the ionic liquid and chalcone that prevents the reduction of carbonyl group.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%